2018
DOI: 10.7150/jca.22968
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study on the prevalence and comparative analysis of metabolic syndrome and its components among Chinese breast cancer women and control population

Abstract: Metabolic syndrome has been previously identified as a risk factor for breast cancer and is increasingly a public health concern. This study aims to investigate the prevalence of metabolic syndrome and its components among primary breast cancer and control population. The clinical data of metabolic syndrome and its components in the breast cancer (605 cases) and control population (3212 cases), from Breast Cancer Center and Physical Examination Center of Chongqing, China, from July 2015 to February 2017, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 36 publications
11
15
0
Order By: Relevance
“…In this study, the prevalence of MetS among cancer survivors was 34.1% which is consistent with the findings of a previous study [ 19 ]. However, there were significant differences in the reported prevalence of MetS among cancer patients in another previous study [ 20 ], which reported the differences in the prevalence of MetS among women with breast cancer according to tumor stage.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the prevalence of MetS among cancer survivors was 34.1% which is consistent with the findings of a previous study [ 19 ]. However, there were significant differences in the reported prevalence of MetS among cancer patients in another previous study [ 20 ], which reported the differences in the prevalence of MetS among women with breast cancer according to tumor stage.…”
Section: Discussionsupporting
confidence: 93%
“…This difference can be attributed to the variation in breast cancer survival duration and ethnic composition percentage among the breast cancer survivors between these two studies. Furthermore, MetS prevalence among breast cancer survivors as reported in the current study was also similar, or higher than the data reported in other countries such as India -NCEP ATP III definition: 40.0% vs 40.0% respectively (Wani et al 2017), China -Harmonized definition: 50.5% vs 32.6% (Wu et al 2018), Korea -Harmonized definition: 50.5% vs 43.9% (Lee et al 2013), USA -Harmonized: 50.5% vs 26.1% (Calip et al 2014), Denmark -NCEP ATP III definition:…”
Section: Discussionsupporting
confidence: 87%
“…Similar to the findings of previous research, this study reported significant links between MetS and increased body weight (Ching et al 2018;Moreira et al 2014;Ortiz-Rodríguez et al 2017), waist circumference (Johari and Shahar 2014;Ortiz-Rodríguez et al 2017;Raposo et al 2017), body fat percentage (Johari and Shahar 2014;Ortiz-Rodríguez et al 2017) and BMI (Wu et al 2018). However, we did not find a significant difference across MetS status in any specific sociodemographic profile, total cholesterol level or LDL-c level.…”
Section: Contrarilysupporting
confidence: 90%
See 1 more Smart Citation
“…(2) TG ≥150 mg/dL and/or HDL-C < 40 mg/dL and/or the use of antihyperlipidemic medication; (3) fasting blood glucose ≥110 mg/dL (with a fasting duration of ≥3 h), or casual blood glucose (for < 3 h or without regard to the time since the last meal) ≥140 mg/dL and/or the use of antidiabetic medication. In some Chinese studies, experts defined the cutoff of waist circumference as 80 cm for females [17]. Forest plot assessing the risk of breast cancer incidence associated with the metabolic syndrome according to the study type (cohort study or case-control study).…”
Section: Definition Of Metsmentioning
confidence: 99%